Development of Religious Moderation Study on Prevention of Radicalism in Indonesia: A Systematic Literature Review Approach - Ahmad Nailul Murad; Darlin Rizki (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This article aims to record the development of literature on religious moderation and its efforts to prevent radicalism. The research method used is Systematic Literature Review (SLR), which is a method of collecting several articles, identifying, analyzing data, and conducting a critical review of the collected research data. The results of this study are known that the development of religious moderation studies to eradicate radicalism has been limited over the past five years. Previous researchers tend to develop more literature studies, while field research is only centralized in educational institutions. Two tendencies of researchers examine this topic, namely first the study of texts or narratives, the existing research dismantles radical ideas that are veiled in society through counter-religious texts. Second, in the field, researchers agree that educational institutions are a potential forum for the spread of radical understanding. In the future, the authors can conduct further investigations on the empirical spread of radicalism among young people, especially social media users.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//